Peran Perguruan Tinggi dalam Mendorong Inovasi Pertanian Berkelanjutan untuk Ketahanan Pangan di Era Sustainable Development Goal - Annisa Kesuma Wardani (Unri Conference Series: Community Engagement, 2025)
In the SDGs agenda, food security is a key goal that demands continuous innovation in the agricultural sector. As centers of science and technology creation, universities have a mandate to develop agricultural practices that are environmentally friendly, resource-efficient and adaptive to climate change. This research explores the role of universities in designing and disseminating innovations that strengthen food security at the national level. The method used is literature analysis and qualitative description of the best examples from various universities across Indonesia. The findings show that universities' contributions stand on three main pillars: research, education and community service. Among the innovations produced are precision agriculture technologies, integrated farming systems, and community-based farmer empowerment models. Nonetheless, a number of challenges, especially the lack of collaboration between sectors and the slow adoption of technology among farmers, hinder the expansion of impact. Therefore, strengthening the synergy between universities, government and industry is key to accelerating the implementation of sustainable agriculture that supports food security across the country.